Sustainable Creative Economy in Cities: Comparative Analysis of Capital Cities in the EU - Hojnik, Barbara Bradač (Problemy Ekorozwoju, 2019)
This article compares levels of creative economies in capital cities in European Union (EU), identifies groups of cities with similar characteristics, and approaches to developing a sustainable creative cities. At the urban level, creativity represent an important element of economic activity, enable the development of creative cities and contribute to all pillars of sustainable development. An essential aspect of creative economy is its quantity and quality in a particular area, which is often measured by the extent of cultural and creative industries and some other indicators. Therefore, in the article, creative economy is analysed by three indicators (Cultural vibrancy, Creative economy and Enabling environment) to assess and compare its levels in capital cities in EU. Data were collected from the database of the Cultural and Creative Cities Monitor. The comparison of capital cities by three indicators identified four groups of cities according the differences in their developmental levels of creative economy. The findings show that the differences and the relative performance regarding the creative economy among capital cities in EU are still remarkable, and that particular groups of cities focus and consequently sustainably develop specific aspects of creative economy.